Freedom Of Speech Para Demonstran: Bukan Sekedar Dilema Perlindungan Hukum? - Ahmad Jamaludin (Universitas Islam Nusantara, 2020)
Democracy has an important meaning in a state principle which in fact in its implementation has differences from each country that adheres to it. This fundamental democratic idea provides a new concept of the rule of law in which there are principles of the rule of law. Democracy and human rights are requirements for the implementation of the rule of law, democracy and the protection of human rights can be said to be access to democratization which guarantees all forms of political freedom. Not only freedom in terms of politics, freedom of opinion and expression today is also a basic right that in essence must be given to all human beings in a democratic country. All forms of freedom of opinion that are owned by individuals and/or legal entities as legal subjects in the life of society, nation and state require guarantees for freedom of assembly, association and expression as described in Law Number 39 of 1999 concerning Human Rights. Protection and guarantees for these freedoms are needed in the practice of demonstrations, as a movement to express opinions in public in the form of dynamic dialogue and political suppression efforts with the aim of advancing people's way of thinking towards a democratic state. This paper analyzes the juridical review of freedom of expression in public carried out by a group of demonstrators as a guarantee of the rights of every Indonesian citizen, which is then linked to Law Number 39 of 1999 concerning Human Rights. In the results of the analysis, the practice still needs a lot of evaluation in terms of supervision which should be more stringent through coordination related to human rights enforcement, especially in terms of expression. There is a guarantee of freedom to interact without being limited by undemocratic political policies and there must be continued advocacy regarding the importance of upholding human rights and the tolerant attitude of the community towards everyone's freedom of expression.Demokrasi memiliki arti penting dalam sebuah asas kenegaraan yang nyatanya dalam pelaksanaannya memiliki perbedaan dari setiap negara yang menganutnya. Gagasan demokrasi yang bersifat fundamental ini memberikan konsep baru mengenai negara hukum yang didalamnya terdapat prinsip negara hukum. Demokrasi dan HAM merupakan persyaratan bagi penyelenggaraan negara hukum, demokrasi dan perlindungan HAM dapat dikatakan merupakan akses adanya demokratisasi yang menjamin segala bentuk kebebasan politik. Tidak hanya kebebasan dalam hal politik, kebebasan dalam berpendapat dan berekspresi dewasa ini juga merupakan hak dasar yang pada hakikatnya harus diberikan kepada seluruh insan negara demokratis. Segala bentuk kebebasan berpendapat yang dimiliki orang dan/atau badan hukum sebagai subjek hukum dalam hidup bermasyarakat, berbangsa, dan bernegara diperlukan adanya jaminan atas kebebasan berkumpul, berserikat dan menyatakan pendapat sebagaimana dijelaskan dalam Undang-Undang Nomor 39 Tahun 1999 tentang Hak Asasi Manusia. Perlindungan serta jaminan atas kebebasan tersebut diperlukan dalam praktik demontrasi, sebagai gerakan menyatakan pendapat di muka umum dengan bentuk dialog dinamis dan upaya penekanan secara politik dengan tujuan kemajuan cara berpikir masyarakat menuju negara yang demokratis. Tulisan ini menganalisis tinjauan secara yuridis mengenai kebebasan berpendapat di muka umum yang dilakukan oleh sekelompok demonstran sebagai jaminan hak setiap warga negara Indonesia, yang kemudian dihubungkan dengan Undang-Undang Nomor 39 Tahun 1999 tentang Hak Asasi Manusia. Pada hasil analisis, praktiknya masih perlu banyak evaluasi dalam hal pengawasan yang seharusnya dapat lebih ketat melalui koordinasi terkait penegakkan HAM khususnya dalam hal berekpresi. Adanya jaminan kebebasan berinteraksi tanpa di batasi oleh kebijakan politik yang tidak demokratis dan harus terus dilakukan advokasi mengenai pentingnya penegakkan HAM dan sikap toleran masyarakat terhadap kebebasan berekspresi setiap orang.